The effect of wrist splint on grasp strength in patients with idiopathic carpal tunnel syndrome - Masoud Rafiaei; Sanaz Shirani; Solmaz Shirani (Vesnu Publications, 2011)
Introduction: carpal tunnel syndrome is one of the most common causes of wrist pain in middle-aged people with consequent problems in wrist movements. This syndrome is more prevalent in women than in men. The carpal tunnel syndrome is caused by blockage of median nerve in carpal tunnel. During moving hands, affected people may feel numbness and tingling which may eliminate by depression from the median nerve. Determine the effect of wrist support splint on grasp strength in patient with idiopathic carpal tunnel syndrome. Method: twenty-eight patients with carpal tunnel syndrome were first evaluated and then randomly assigned to intervention and control groups of 14 subjects each. Subjects in the first group (intervention) were given the wrist splint while those in the second group (control) did not receive any splint. The rate of the disease signs, syndrome intensity and grasp strength were measured and recorded three weeks before starting the study and re-evaluated three week after the completion of the program. The Visual Analogue Scale was applied for measuring pain levels and syndrome intensity was assessed through a questionnaire. Grasp strength was evaluated by a dynamometer. Results: In intervention group, a significant decrease in the rate of disease signs and in the intensity of syndrome was observed along with a significant increase in grasp strength. Conclusion: According to the study's results, using a wrist-support splint results in decrement of the diseases signs and syndrome intensity and also in improved grasp strength as well as the efficiency of wrist. Key words: carpal tunnel syndrome, grasp strength, pain, Body Mass Index